DEVELOPMENT OF THE DIGITAL ECONOMY IN UZBEKISTAN: A SHORT PATH TO DEVELOPMENT (Conferencea, 2023)
Humanity is experiencing an important period associated with the transformation of economic sectors, digitization, mobilization of this process, and the introduction of artificial intelligence into the field. The need to develop a new economy becomes even more clear in a situation where by 2022 almost a quarter of the world's GDP will be accounted for by the digital sector. In developed countries, the implementation of the digital economy has already begun. In the conditions of the globalization of the world economy and the development of technologies, the economic development of Uzbekistan cannot be achieved without the development of the digital economy [1-4].